1994
DOI: 10.1104/pp.106.4.1347
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of the Gene Encoding Glutamine-Dependent Asparagine Synthetase in Arabidopsis thaliana

Abstract: Here, we characterize a cDNA encoding a glutamine-dependent asparagine synthetase (ASN7) from Arabidopsis thaliana and assess the effects of metabolic regulation on ASNl mRNA levels. Sequence analysis shows that the predicted ASNl peptide contains a purFtype glutamine-binding domain. Southern blot experiments and cDNA clone analysis suggest that ASNl is the only gene encoding glutamine-dependent asparagine synthetase in A. thaliana. The ASNl gene is expressed predominantly in shoot tissues, where light has a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
241
1
7

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(262 citation statements)
references
References 41 publications
(57 reference statements)
13
241
1
7
Order By: Relevance
“…In higher plants, sugars affect growth and development throughout the life cycle, from germination to flowering to senescence (Steeves and Sussex, 1989;Brusslan and Tobin, 1992;Graham et al, 1992;Bernier et al, 1993;Sheen, 1994;Thomas and Rodriguez, 1994;Dangl et al, 1995). Recently, it has become apparent that sugars are physiological signals repressing or activating plant genes involved in many essential processes, including photosynthesis, glyoxylate metabolism, respiration, starch and sucrose synthesis and degradation, nitrogen metabolism, pathogen defense, wounding response, cell cycle regulation, pigmentation, and senescence (Chen et al, 1994;Knight and Gray, 1994;Lam et al, 1994;Sheen, 1994;Herbers et al, 1995;Mita et al, 1995;Reynolds and Smith, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In higher plants, sugars affect growth and development throughout the life cycle, from germination to flowering to senescence (Steeves and Sussex, 1989;Brusslan and Tobin, 1992;Graham et al, 1992;Bernier et al, 1993;Sheen, 1994;Thomas and Rodriguez, 1994;Dangl et al, 1995). Recently, it has become apparent that sugars are physiological signals repressing or activating plant genes involved in many essential processes, including photosynthesis, glyoxylate metabolism, respiration, starch and sucrose synthesis and degradation, nitrogen metabolism, pathogen defense, wounding response, cell cycle regulation, pigmentation, and senescence (Chen et al, 1994;Knight and Gray, 1994;Lam et al, 1994;Sheen, 1994;Herbers et al, 1995;Mita et al, 1995;Reynolds and Smith, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…1995) findings in maize suggest that NAD(H)-GDH isoenzymes are encoded by more than one gene. Furthermore, the presence of multiple genes encoding for enzymes involved in nitrogen metabolism appears to be a common occurrence in A. thaliana, and small multigene families encoding for GS (Peterman and Goodman, 1991), GOGAT (Lam et al, 1995a), Asn synthetase (Lam et al, 1995a(Lam et al, , 1995b, and aspartate aminotransferase (Schultz and Coruzzi, 1995;Wilkie et al, 1995) have been reported. Our findings confirm the existence of a small gene family encoding NAD(H)-GDH.…”
Section: Dlscusslonmentioning
confidence: 99%
“…This results in efficient biosynthesis of Gln, which is further transaminated into aspartate. However, these metabolic signals also repress the expression of the gene encoding Asn synthetase, blocking further conversion of aspartate into Asn Coruzzi, 1990, 1991;Lam et al, 1994Lam et al, , 1995Chevalier et al, 1996) In contrast, at night, when the carbon-to-nitrogen ratio is relatively low, dark and relatively high nitrogen levels stimulate the expression of Asn synthetase, resulting in efficient conversion of aspartate into Asn (Lam et al, 1995). Our previous (Zhu- Shimoni et al, 1997) and present reports showed further that the conversion of aspartate into Asn or into aspartate family amino acids is also subject to a coordinated, reciprocal metabolic regulation of the expression of AK/HSD and Asn synthetase genes.…”
Section: Coordinated Metabolic Regulation Of Ak/hsd Gene Expression Amentioning
confidence: 99%
“…The metabolism of Gln, glutamate, aspartate, and Asn is subject to a coordinated metabolic regulation. Whereas the expression of an Arabidopsis and pea Gln synthetase was shown to be stimulated by light (Lam et al, 1994(Lam et al, , 1995, the expression of an Arabidopsis Asn synthetase was repressed by light and Suc, and stimulated by dark and nitrogen Coruzzi, 1990, 1991;Lam et al, 1995;Chevalier et al, 1996). It has been suggested that during the day plants accumulate Gln, glutamate, and aspartate, which are apparently used for the synthesis of other amino acids, whereas during the night, aspartate is converted into Asn for storage (Galili, 1995;Lam et al, 1995).…”
mentioning
confidence: 99%